Complete Blood Cells Findings Among Covıd-19 In-Patients at Covıd-19 Reference Hospitals, West Nusa Tenggara - Arjita, I Putu Dedy; Sabariah, Sabariah; Anulus, Ayu (Medical Laboratory Technology Journal, 2020)
Covid-19 virus still attacks various worldwide sectors, especially health. The current problem is that the Covid-19 vaccine is still in progress, so the best strategy to deal with this problem is to prevent this disease's spread. In the laboratory sector, complete blood cells tend to use as a screening method for disease, especially infectious disease. This study describes the CBCs findings among Covid-19 patients at Covid-19 reference hospitals in West Nusa Tenggara. This study will enhance the data to provide early diagnosis for patients with Covid-19. This was a retrospective study conducted from Mei to July 2020. A total of four hospitals have access to 85 medical records of Covid-19 patients. The patient’s data included in this study should have (1) initials; (2) Gender; (3) Age; (4) Patients' disease other than Covid-19; and (5) The results of the first CBCs examination. Incomplete data excluded from the study. The CBCs data collected from Hospital Management Information Systems (HMIS) and Laboratory Information Systems (LIS). The data were analyzed descriptively. The results showed that 5.88% of patients with comorbidities or another disease reported abnormal CBCs results. In comparison, another 94.12% of patients without another disease than Covid-19 tend to present normal results. In conclusion, most of the CBC's findings among Covid-19 patients in West Nusa Tenggara show normal value among patients with no disease other than Covid-19.